Time‐varying effects of 'optimized smoking treatment' on craving, negative affect and anhedonia. (1st October 2020) - Kim, Nayoung; McCarthy, Danielle E.; Cook, Jessica W.; Piper, Megan E.; Schlam, Tanya R.; Baker, Timothy B.
Abstract: Aims: To identify when smoking cessation treatments affect craving, negative affect and anhedonia, and how these symptoms relate to abstinence, to help evaluate the effects of particular intervention components in multi‐component treatments and accelerate treatment refinement. Design: Secondary analysis of data from a two‐arm randomized controlled trial. Setting: Seven primary care clinics in Wisconsin, United States. Participants: Adult primary care patients who smoked daily ( n = 574). Intervention and comparator: Intervention was abstinence‐optimized treatment (A‐OT, n = 276) comprising 3 weeks of nicotine mini‐lozenges pre‐target quit day (TQD), 26 weeks of combination nicotine patch and mini‐lozenges post‐TQD and extensive psychosocial support. The comparator was recommended usual care (RUC, n = 298), comprising brief counseling and 8 weeks of nicotine patch post‐TQD. Measurements: Time‐varying effect models examined dynamic effects of A‐OT (versus RUC) on the primary outcomes of nightly cigarette craving, negative affect and anhedonia from 1 week pre‐ to 2 weeks post‐TQD. Exploratory models examined within‐person relations between nicotine medication use and same‐day symptom ratings. Secondary logistic regression analyses examined associations between post‐TQD craving, negative affect and anhedonia and 1‐month post‐TQD abstinence. Findings: A‐OT significantly suppressed pre‐ and post‐TQD craving (β = −0.27 to −0.46 across days) and post‐TQD anhedonia (β = −0.24 to −0.38 across days), relative to RUC. Within individuals, using patches was associated with lower negative affect in RUC (β = −0.42 to −0.52), but not in A‐OT. Using more mini‐lozenges was associated with greater craving (β = 0.04–0.07) and negative affect (β = 0.03–0.05) early, and with lower anhedonia (β = −0.06 to −0.12) later. Greater post‐TQD craving (OR = 0.68) and anhedonia (OR = 0.85) predicted lower odds of abstinence 1 month post‐TQD. Conclusion: Time‐varying effect models showed that a multi‐component treatment intervention for smoking cessation suppressed significant withdrawal symptoms more effectively than recommended usual care among daily adult smokers motivated to quit. The intervention reduced craving pre‐ and post‐target quit day (TQD) and anhedonia post‐TQD.